An Exploration of the Impact of Sociocultural Context on Language Learning towards EFL Learners: A Qualitative Case Study - Xing, Qidan (Journal of Educational Research and Policies, 2025)
Recent years have witnessed the abundant research on socio-cultural theory (SCT) in area of second language acquisition (SLA) and second language learning (SLL). The pedagogical practice based on SCT also brings considerable discussions and ongoing innovations. The current study, with theoretical basis of SCT, aims to investigate how sociocultural context facilitates EFL learners and how such factor impacts on their way of thinking and language development. Data was collected by interviews from three Chinese EFL learners with background of studying and working in an English-speaking country. The findings suggest that EFL learners are given the opportunities to actively use language when immersed in target language environment. Moreover, the school and workplace settings do provide a platform where EFL learners have access to social interactions and cultural practices, which also unconsciously influences their thinking patterns and language development.